Re-instatement of Bulbostylis tisserantii (Cyperaceae) an ignored species from Central Africa - Mesterházy, Attila; Verloove, Filip (Phytotaxa, 2020)
Bulbostylis viridecarinata (De Wild.) Goetgh. is a widespread species occurring in many parts of Tropical Africa. Bulbostylis tisserantii Cherm. was synonymized with this species but based on numerous morphological differences this species should be re-instated at species rank. It is only known from three collections, all originating in the southern part of the Central African Republic. Descriptions and conservation status for both species are provided and their main distinguishing features are opposed and illustrated. Lectotypes are designated for Bulbostylis fasciculata Cherm. and Fimbristylis tisserantii Cherm.